1985
DOI: 10.1093/oxfordjournals.aje.a113972
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia as a Risk Factor of Coronary Heart Disease: The Framingham Study

Abstract: Uric acid values were obtained on subjects of the original Framingham cohort at their fourth and 13th biennial examinations. The mean uric acid value for men was 5.0 mg/dl at the fourth examination and 5.7 mg/dl at examination 13 and was 3.9 mg/dl and 4.7 mg/dl, respectively, for women. This secular trend was due to both "laboratory drift" and increasing use of diuretics. Serum uric acid values were consistently higher in subjects of both sexes who were taking antihypertensive drugs at both examinations. Serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
190
1
17

Year Published

1991
1991
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 360 publications
(232 citation statements)
references
References 0 publications
24
190
1
17
Order By: Relevance
“…[2][3][4][5][6][8][9][10][11][12]17 The question as to whether high disease which could confound the observed association. This review assesses the role of elevated serum uric acid as an independent role for coronary heart disease.…”
Section: Serum Uric Acid and Coronary Heart Diseasementioning
confidence: 99%
See 4 more Smart Citations
“…[2][3][4][5][6][8][9][10][11][12]17 The question as to whether high disease which could confound the observed association. This review assesses the role of elevated serum uric acid as an independent role for coronary heart disease.…”
Section: Serum Uric Acid and Coronary Heart Diseasementioning
confidence: 99%
“…6 By contrast the Framingham Study found the relation to be independent of antihypertensive treatment but the relationship was attenuated upon adjustment for other cardiovascular risk factors including blood pressure and cholesterol. 4 The NHANES study 12 and the Chicago Heart Association Detection Project in Industry 8 both found the relation between uric acid and risk of CHD in men to be attenuated after adjustment for a range of other cardiovascular risk factors, but neither of these studies ascertained which factors were responsible for the attenuation. The Social Insurance Institution of Finland Study observed the relationship to be confounded by pre-existing CHD.…”
Section: Serum Uric Acid and Coronary Heart Diseasementioning
confidence: 99%
See 3 more Smart Citations